1993
DOI: 10.1055/s-2007-1021177
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light, Moderate and Severe Bicycle Exercise on Lymphocyte Subsets, Natural and Lymphokine Activated Killer Cells, Lymphocyte Proliferative Response and Interleukin 2 Production

Abstract: The purpose of the present study was to evaluate the effect of acute bicycle exercise at different exercise intensities on the immune system. Six healthy volunteers exercised on a bicycle ergometer for 1 h at 25%, 50% and 75% of VO2max with an interval of 2 to 3 weeks. Blood samples were collected in the basal state, at the end of exercise and 2 h later. The absolute concentrations of all lymphocyte subsets increased during and fell after exercise at 50% and 75% of VO2max, but did not change significantly at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
4
18

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 11 publications
7
55
4
18
Order By: Relevance
“…These results were similar to those described in previous studies. 4 Study limitation Subject numbers were marginal in the present experiment. However, several studies have examined exercise immunology in able-bodied subjects, and the subject numbers in some of these well-controlled studies were less than 10 persons.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These results were similar to those described in previous studies. 4 Study limitation Subject numbers were marginal in the present experiment. However, several studies have examined exercise immunology in able-bodied subjects, and the subject numbers in some of these well-controlled studies were less than 10 persons.…”
Section: Discussionmentioning
confidence: 93%
“…However, several studies have examined exercise immunology in able-bodied subjects, and the subject numbers in some of these well-controlled studies were less than 10 persons. 4,6,15 Furthermore, it was difficult to recruit individuals with SCIs who met the strict inclusion criteria of the present study including completion of the 2-h arm crank ergometer exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are rapidly recruit to the peripheral blood probably, via shear stress due to increase in blood flow added with a catecholamine--induced 20 down regulation of adhesion molecule expression. This increase in the peripheral pool has been associated with increased immune surveillance 21 .Despite of that, during prolonged exercise, circulating NK cells counting may decrease below the pre-exercise values 22 , in which the cells leave the peripheral blood circulation possibly to enter sites of muscle damage 23 . Cells exit from circulation or inhibition of their entrance may mean that these cells, especially the more cytotoxic subgroup, are extra or transiting to sites where they are needed for immune or inflammatory function.…”
Section: Discussionmentioning
confidence: 99%
“…Although many previous findings [12,14,15,[80][81][82][83] support the increase in circulating NK cell count during progressive exercise as well as the rapid post-exercise NK cell recovery, however, the experiment by Del Giacco et al [51] showed that the number of NK cells at the maximum workload did not further increase with respect to their number counted at VO 2-AT . This fact probably meant that when the contribution from anaerobic sources for exercising muscles became relevant (i.e.…”
Section: Nk Cells and Pro-inflamatory/ Anti-inflamatory Adverse Me-chmentioning
confidence: 92%